Decent and affordable housing in Rwanda - MUNYEMANA, Emmanuel (KDI School, 2016)
Spread of informal settlements constitutes an indication that households are unable to afford a decent housing. For several years housing market in Rwanda was left free of government intervention which raised issue of inclusiveness. Using mixed research methods, this paper explored the underlying factors beyond income that affect households to access decent and affordable housing and also reviewed housing policies of successful countries in providing housing to low and middle income people. Key findings revealed that in urban areas of Rwanda, informal or squatter settlements represent 55.7% and unplanned setting, also, 49.9% of households in urban areas live in privately rented housing. Furthermore, 56.4% of housing in urban and 92.0% of housing in rural areas were not decent, while, 33.2% of households in urban area confront affordability challenges. Only 27.7% of households in urban and 6.2% of households in rural areas live in decent and affordable housing. Employment in skilled occupations, owning livestock(s), and, having non-farm enterprises strongly contribute to having decent and affordable housing. However, households owning money to others and married couples have high likelihood of living in non decent housing and confront housing hardships. Reviews of successful countries in housing for low income households indicated that government interventions based on income and other demographic differentials resulted into improvement in supply of housing and lessening affordability burden to households.
Thesis(Master) --KDI School:Master of Public Policy,2016